Teknik “Suku Kata Tapak Tangan” dalam Membantu Meningkatkan Kemahiran Suku Kata KVKV dalam Kalangan Kanak-Kanak Prasekolah - Monnas, Latifah (Selangor Humaniora Review, 2018)
The aim of this action research is to explore how far “using the palm technique” help preschoolers improve their mastery of the CVCV syllables. The study was conducted among preschoolers from the Sri Murni Preschool, IPG Tawau. The focus of the research is to observe the preschoolers using the palm technique in their reading skills of the CVCV syllables. Observation and interviews were used in this qualitative approach as tools to collect data. The findings show that preschool children were able to read the CVCV syllables faster. This technique is not only easy and fun to use but also help developed children’s sensory abilities. It is also simple and cost effective for preschool teachers to use.